(untitled) (Revista cientifica In Vestigium Ire, 2018)
Gender inequality in the labor market in Colombia has not been studied from the perspective of orthodox economic theory, and so the relevance of the analysis of the care economy and classical microeconomics in which the perspective of the use of time by the economic agents is conjunctural for the labor market. For this reason, this article expects to find gender inequality for the 2012-2013 period in Colombia, reflected in the greater demand there is for men in paid activities and, conversely, for women in domestic activities.